PENGARUH KOMPETENSI MANAJERIAL KEPALA SEKOLAH DAN MOTIVASI GURU, TERHADAP PRESTASI SISWA SD NEGERI SEKECAMATAN PULAU RIMAU - Riyanto, Tobing; Masniar, Masniar (Graduate Program Magister Manajemen Pendidikan, 2019)
This study aims to reveal: (1) the influence of principals' managerial competencies on student achievement; (2) the effect of principals' managerial competencies on student achievement through teacher achievement motivation; (3) the influence between teacher achievement motivation and student achievement. This research is an ex-post facto study, with a population of 20 teachers from Rimau Island SDN 32 and a sample of 10 people selected by proportional sampling technique. The instrument of data collection is a questionnaire. Data analysis used path analysis techniques to test the research hypothesis. The results of the study show that: (1) there is the influence of principals' managerial competencies with student learning achievement 6.52%; (2) the influence between teacher achievement motivation and student achievement through teacher achievement motivation 32.12%; (3) there is a direct influence between teacher achievement motivation and student learning achievement 46.06%. So overall managerial competence of principals, teacher achievement motivation towards student learning achievement is 84.70%. This means that if the quality of the principal's managerial competence and teacher achievement motivation is improved, it will be able to improve the learning achievement of students at SDN 32 Rimau Island.